SKL1 Is Essential for Chloroplast Development in Arabidopsis - Xu, Huimin; Zhang, Liwen; Li, Ruili; Wang, Xinwei; Liu, Shuai; Liu, Xiaomin; Jing, Yanping; Xiao, Jianwei (Frontiers in Plant Science, 2018)
The Arabidopsis shikimate kinase-like 1 (skl1-8) mutant is characterized by a pigment-defective phenotype. Although the related phenotypical defect mainly has been attributed to the blocking of chloroplast development, the molecular functions of SKL1 remain largely unknown. In this study, we combined multiple approaches to investigate the potential functions of SKL1. Results showed that the skl1-8 mutant exhibited an albino phenotype and had a dramatically reduced chlorophyll content as a consequence of a single nuclear recessive gene mutation. Chemical complementation analysis indicated that SKL1 does not function as SK proteins in the shikimate pathway. In addition, by chlorophyll fluorescence parameters and immunoblot analysis, the levels of photosynthetic proteins are substantially reduced. Moreover, by transcriptome analysis, specific groups of nuclear genes involved in photosynthesis, such as light-harvesting complex, pigment metabolism, carbon metabolism, and chloroplast gene expression, were down-regulated, whereas several defense and oxidative stress responsive genes were up-regulated in the skl1-8 mutant compared with the wide type. Furthermore, we found the expression of genes related to auxin transport and response was repressed in the skl1-8 mutant, probable suggesting that SKL1 is involved in auxin-related pathways during chloroplast development. Together, these results provide a useful reference for characterization of SKL1 function during chloroplast biogenesis and development.